2017
DOI: 10.1177/1350650117739764
|View full text |Cite
|
Sign up to set email alerts
|

Performance of lubricating oils for wind turbine gear boxes and bearings

Abstract: In this study, the friction and wear properties of six different new and used wind turbine gear oils (ISO VG 320), with different base oil formulations and additives packages, were investigated. For that purpose, a four-ball tribometer and an Optimol SRV were used. Moreover, the lubricants extreme pressure properties were also evaluated, using the same four-ball tribometer. The study also includes a characterization of the lubricants. The main objective was to compare the new and used gear oils in order to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The coefficient of friction (COF) 16 between pairs is analysed by tribometer. It is found that the COF increases with an increase in running time 16,17 . viscosity of oil reduces with an increase in running hours.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…The coefficient of friction (COF) 16 between pairs is analysed by tribometer. It is found that the COF increases with an increase in running time 16,17 . viscosity of oil reduces with an increase in running hours.…”
Section: Introductionmentioning
confidence: 87%
“…In the present case, considering two control factors (load and speed) with three-level, such as 30, 40, 50 N for load and 300, 400 and 500 rpm for speed the L 9 orthogonal array, the Taguchi configuration of the experiment was chosen, as shown in Table 7. 13,14,[16][17][18][19][20][21][22][23]26,[40][41][42][43][44][45][46][47][48] The weight loss is recorded for pin and disc (both). Five tests are conducted under each condition and average value are taken.…”
Section: Design Of Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lubricating oil, which reflects the system performance in the full life cycle through its properties, 1 should be monitored and replaced appropriately to maintain the service life of machines in a good condition. 2,3 Oil wear analysis and lubrication quality analysis have been widely accepted and performed to describe oil deterioration and machine failure in practical operations 47 . Wear particles in lubricated tribo-systems can cause wear increment and accelerate oil deterioration.…”
Section: Introductionmentioning
confidence: 99%